Congenital syphilis in Brazil: a reality to be faced (Research, Society and Development, 2020)
The objective was to analyze by means of scientific evidence, how the congenital syphilis is dealt with in the scope of Primary Care, identifying the measures adopted in this context. An integrative literature review study was conducted using the databases of the platforms: Virtual Health Library (VHL), Online Medical Literature Search and Analysis System (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and Nursing Database (BDENF). The descriptors were used: “Congenital syphilis”; "Syphilis"; “Prenatal Assistance” connecting to the Boolean operator “AND”. In total, 340 articles were found, which when submitted to the inclusion and exclusion criteria, only 80 articles remained for analysis of the abstract. After reading the abstracts, 15 articles were selected to be included in the paper. The results of the study demonstrated that low socioeconomic conditions, absence or discontinuation of prenatal consultations of the pregnant woman and her partner, low education, inadequate diagnosis and treatment, lack of medication (benzathine penicillin), disqualified professionals and absence of compulsory notification, are factors that are directly interconnected in coping with congenital syphilis in primary care. It is concluded that the active search, with screening of the population included in this research, must be carried out, working on new health education strategies and public policies to reach mainly pregnant women who are more vulnerable to this damage, reinforcing through guidance, lectures and discussion groups the importance of adherence to prenatal care and early treatment of sexually transmitted infections such as syphilis.